A review of traditional cost system versus activity based costing approaches - M. Towati Altawati, Nawal Omar; Ng, Kim-Soon; Ahmad, Abd Rahman; Elmabrok, Ali Abusalah (American Scientific Publishers, 2018)
In the last two decades, business environment has been changing rapidly with fierce global competition. Firms using the traditional costing system were forced to change from their old system traditional-cost method and to accept the newer cost system, better known as the activity based on costing (ABC system). The new system is able to support and enhance decision making of the decision makers, besides being adaptable to the new business environment. Therefore, this paper aimed to review the applications and importance of both traditional cost system and ABC system for business decision making, and compare the results of ABC and the traditional costing systems via literature reviews of works by previous authors. The results reflected that activity based on the costing system is a better system comparing to the traditional costing systems. ABC system enhances decision making of the interested user with its better adaptable costing features to support the new business environment and global business competition. It thus creates a more sustainable source of competitive advantage. In addition, it identifies the under-costed and over-costed of the products of a firm.